An updated checklist of chondrichthyans of Calabria (Central Mediterranean, southern Italy), with emphasis on rare species - LEONETTI, FRANCESCO L.; GIGLIO, GIANNI; LEONE, AGOSTINO; COPPOLA, FABRIZIO; ROMANO, CHIARA; BOTTARO, MASSIMILIANO; REINERO, FRANCESCA R.; MILAZZO, CONCETTA; MICARELLI, PRIMO; TRIPEPI, SANDRO; SPERONE, EMILIO (Mediterranean Marine Science, 2020)
In this contribution the checklist of chondrichthyans of Calabria (Central Mediterranean, southern Italy) is reported. Data presented is derived from twenty years of opportunistic and active surveys from 2000 to 2020. A total of 55 species of chondrichthyans is present in Calabrian seas: 33 sharks, 20 rays, and 2 chimaeras. These species represent approximately 62% of the total reported for the Mediterranean. Approximately 71% of Calabrian species have been reported in the Tyrrhenian Sea, 49% in the Ionian Sea, and 33% in the Strait of Messina. According to IUCN criteria, new records of Endangered and Critically Endangered species (i.e., Carcahrodon carcharias [Linnaeus, 1758], Lamna nasus [Bonnaterre, 1788], Cetorhinus maximus [Gunnerus, 1765], Mobula mobular [Bonnaterre, 1788], Sphyrna zygaena [Linnaeus, 1758]) are reported, together with the first record of Raya brachyura Lafont, 1873 for the Ionian coasts and probably third confirmed record of the rare chimaera Hydrolagus mirabilis (Collett, 1904) for the Mediterranean.